2021
DOI: 10.4252/wjsc.v13.i7.894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shear stress on differentiation of stem cells into endothelial cells

Abstract: Stem cell transplantation is an appealing potential therapy for vascular diseases and an indispensable key step in vascular tissue engineering. Substantial effort has been made to differentiate stem cells toward vascular cell phenotypes, including endothelial cells (ECs) and smooth muscle cells. The microenvironment of vascular cells not only contains biochemical factors that influence differentiation but also exerts hemodynamic forces, such as shear stress and cyclic strain. More recently, studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 129 publications
0
17
0
Order By: Relevance
“…MSCs are physiologically subjected to interstitial flow that exerts low levels of shear stress that has been shown to impact their growth kinetics as well as differentiation. [ 18,19 ] We designed 3D‐printed scaffolds with a total surface area of 50 cm 2 consisting of a pillared array ( Figure A and Figure S1, Supporting Information) that permitted medium and gas flow through gas permeable tubing (Figure 1C). Computational fluid modeling was carried out for 1, 5, and 10 mL min −1 to evaluate shear stress (Figure 1D) and flow trajectories (Figure 1E) throughout the scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs are physiologically subjected to interstitial flow that exerts low levels of shear stress that has been shown to impact their growth kinetics as well as differentiation. [ 18,19 ] We designed 3D‐printed scaffolds with a total surface area of 50 cm 2 consisting of a pillared array ( Figure A and Figure S1, Supporting Information) that permitted medium and gas flow through gas permeable tubing (Figure 1C). Computational fluid modeling was carried out for 1, 5, and 10 mL min −1 to evaluate shear stress (Figure 1D) and flow trajectories (Figure 1E) throughout the scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…Culture of MSCs in 3D-Printed Scaffold Perfusion Bioreactor MSCs are physiologically subjected to interstitial flow that exerts low levels of shear stress that has been shown to impact their growth kinetics as well as differentiation [27,28]. We designed and 3D-printed scaffolds with a total surface area of 50 cm 2 consisting of a pillared array (Figure 1A) that permitted medium and gas flow through gas permeable tubing (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the scaffold was redesigned to incorporate a pillar configuration previously implemented to create a highly-adaptable and physiologically-relevant microenvironment specifically for human MSCs [40]. In addition, when perfused with media, this design allowed for the use of flow rates that produced shear stress values well below levels previously reported for the in vivo stem cell niche (i.e., 0.1 – 1 dyn/cm 2 ) and well below values known to induce MSC differentiation [27, 29, 41] ( Figure 1D ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that growth factors play an important role in the regulation of endothelial differentiation. 38 The expression of two specific endothelial markers including platelet endothelial cell adhesion molecule-1 (PECAM, CD31) and VEGFR2 was investigated for mesenchymal stem cells cultured on the standard cell plate and electrospun PCL/PGS/gelatin in absent and present of growth factor. The expression of specific endothelial genes of the mesenchymal stem cells seeded on the both samples has been depicted in Figure 5.…”
Section: Expression Of Endothelial Specific Genesmentioning
confidence: 99%